TECTONIC POSITION OF MARBLE MELANGES IN THE EARLY PALEOZOIC ACCRETION-COLLISIONAL SYSTEM OF THE WESTERN PRIBAIKALIE - V. S. Fedorovsky; A. M. Mazukabzov; D. P. Gladkochub (Геодинамика и тектонофизика)
The Early Paleozoic collisional system located in the Olkhon region at the western shores of Lake Baikal resulted from collision of the Siberian paleocontinent and a complex aggregate composed by fragments of a microcontinent, island arcs, back-arc structures and accretionary prisms. The main events were associated with complete manifestation of shear tectogenesis initiated by oblique collision. The current structure includes tectonically displaced components of ancient geodynamic systems that used to have been located dozens and hundreds of kilometres apart. Horizontal amplitudes of tectonic displacement seem to have been quite high; however, numerical data are still lacking to support this conclusion. Information about the structure of the upper crust in the Paleozoic is also lacking as only deep metamorphic rocks (varying from epidote-amphibolite to granulite facies) are currently outcropped. Formations comprising the collisional collage are significantly different in composition and protoliths, and combinations of numerous shifted beds give evidence of a 'bulldozer' effect caused by the collisional shock followed by movements of crushed components of the ocean-continent zone along the margin of the Siberian paleocontinent. As evidenced by the recent cross-section, deep horizons of the Early Paleozoic crust comprise the collisional system between the Siberian craton and the Olkhon composite terrain. A permanent inclusion in the collisional combinations of rocks are unusual synmetamorphic injected bodies of carbonate rocks. Such rocks comprise two groups, marble melanges and crustal carbonate melted rocks. Obviously, carbonate rocks (that composed the original layers and horizons of stratified beds) can become less viscous to a certain degree at some locations during the process of oblique collision and acquire unusual properties and can thus intrude into the surrounding rocks of silicate composition. Such carbonate rocks behave as protrusions or intrusions and contain inclusions of silicate rocks. Formation of marble melanges is a multi-staged process: they occur as early tectonic covers and, more often, accompany shear zones of large lengths, comprise late push-out nappes initiated by shear faults, participate in construction of ring and vortex structures that are generated by shearing in the geological medium of inhomogeneous rheology. In general, the available data give evidence of the fact that formation of synmetamorphic marble melanges is a direct consequence of the oblique collision geodynamics and a sensitive indicator of such a regime. A pure guesswork may suggest that the occurrence of the marble melanges can be associated with a catastrophic loss of viscosity of the carbonate rocks due to a sharp increase of velocities of shear deformations that accompanied the oblique collision.